Workplace bullying among nurses in Saudi Arabia : an exploratory qualitative study : a 152.800 thesis presented in partial fulfilment of the requirements of the degree of Master of Management at Massey University - Alswaid, Eman (Massey University, 2014)
Background: Health-care professionals are among the groups persistently exposed to hostile behaviours in the workplace. It has been well documented that nursing staff in particular are often exposed to workplace bullying, and this is often associated with their stressful and challenging work conditions. Most research on workplace bullying has been undertaken in European countries, North America or Australasia. However, in the Arab region, particularly Saudi Arabia, there is little or no research addressing workplace bullying. Aim: The purpose of this cross-sectional study was to conduct a preliminary investigation into the issue of workplace bullying among nurses working in Saudi Arabia, and gain an understanding of their experiences and perceptions of this issue. Method: Thirty semi-structured interviews were conducted in five public hospitals in Riyadh, Saudi Arabia, with a sample of full-time nurses who had been employed for at least six months. The interviews covered selected concepts derived from relevant literature including work relations; understanding the workplace bullying concept; perceptions of prevalence; antecedents; targets and perpetrators; impact; and management’s response. Interviews were transcribed and thematically analysed using Nvivo 10 computer software. Findings: The study indicated that bullying is a prevalent problem among nurses. There are common meanings attached to bullying and bullying comprises mostly direct or indirect verbal acts. Specific targets of bullying were perceived to included new nurses, certain nationalities, and staff members who were quiet and accepting. Bullying was perceived to be the result of hierarchy and power, discrimination, the work environment, and the targets’ silence. Bullying impacted nurses through psychological outcomes and work- and patient-related outcomes. Different coping strategies, as well as different management responses, were identified in the study. Conclusions: Findings from this study provide evidence for the existence of workplace bullying; participants had both experienced and witnessed bullying as they sought to fit into challenging workplaces. Overlooking the triggers of bullying might put the recruitment and retention of nurses in Saudi hospitals at risk. Management and policy makers in hospitals may benefit from a deeper understanding of workplace bullying, and could help the problem by formulating and implementing prevention strategies. This study serves as a starting point for further research in Saudi Arabia and the Arab region in general.
Keywords: Workplace bullying; Nurses, Saudi Arabia; Nursing, Saudi Arabia